Proteomická analýza nádorových bunek - Tomancová, A; Sedo, O; Zdráhal, Z; Mayer, J; Pospísilová, S (Klinicka onkologie, 2009)
The rapid development of analytical instrumentation and methodical approaches in the course of the last two decades has significantly extended the possibilities of studying proteins in living systems. Proteomic analysis provides ever deeper insights into the molecular nature of biological processes in terms of qualitative and quantitative changes in protein composition in connection with the physiological and pathological states of the organism. Thus, proteomic analysis contributes to a better understanding of these processes and becomes a tool for the development and validation of diagnostic and therapeutic approaches. Thanks to recent achievements, the attention of cancer specialists is more and more focused on human proteome research. In this brief review we explain the principles of widely used proteomic techniques (gel electrophoresis, liquid chromatography, mass spectrometry analysis, protein array technologies) and show examples of their application in oncology, namely hematooncological diseases.
Keywords: Proteome; lidé; nádory; Humans; Neoplasms; Proteomics; proteomika; proteom